THE PATTERNS OF ULTIMATE PLURAL IN THE HOLY QURAN: A SEMANTIC STUDY - Dr. Hafiz Muhammad Sarwar; Dr. Ghulam Ahmad; Dr Makkiah Nabi Bakhsh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The research focuses on the semantic and morphological study of the ultimate plurals by extracting examples from the Holy Quran and their implications. It explores how the ultimate plurals forms are used to convey meaning and significance in the Quranic language. The study analyzes the various forms and structures of the ultimate plurals (????? ??????) in the Quranic context. It also examines the relationship between ultimate plurals forms and the Quranic themes & messages. It also addresses several related linguistic issues depending on the Descriptive, Analytical and Inductive Approaches. The study aims to contribute to a better understanding of the Quranic language and its unique features, particularly in the use of the ultimate plural forms (????? ????? ??????).